Evaluation of CQAs - Banerjee Snehasish (2012)
Search engines have long been recognized as the gateways for online information seeking, but the gradual sophistication of the online information seekers has led to the emergence of Community-based Question-Answering (CQA) sites as an alternative source of information on the Web. There are many CQAs around but their overall effectiveness has not been widely studied. So, the dissertation addresses this problem and attempts to evaluate the overall effectiveness of CQAs based on a three-pronged evaluation framework; consisting of (1) answer quality, (2) answer responsiveness, and (3) corpus comprehensiveness. A total of 500 questions were posted in each of the six CQA sites (Yahoo! Answers, WikiAnswers, Answerbag, Baidu Knows, Tencent Soso Wenwen, Sina iAsk) and the resulting 3000 transactions were examined to conduct a three-way comparison: (1) within languages – English and Chinese; (2) between languages- English versus Chinese; and (3) across all the six individual CQA sites.